Pemerdayaan masyarakat melalui budidaya belut (monopterus albus) alam sebagai mata pencarian alternatif ramah lingkungan masyarakat nelayan Desa Rantau Baru Kabupaten Pelalawan - Nofrizal Nofrizal; Rommie Jhonnerie; Budijono Budijono; Ramses Ramses; Tengku Said Razai (CANANG: Jurnal Pengabdian Masyarakat, 2021)
Rantau Baru Village is one village in the Pengkalan Kerinci sub-district, Pelalawan Regency. The village of Rantau Baru is on the coast of the Kampar River, surrounded by swamp and peat forest areas, so the majority of the population work as traditional fishermen. The income level of traditional fishing communities fluctuates greatly depending on the fishing season. Conditions The difference in the fishing season will affect the level of welfare. One effort that can be done provides other knowledge supplies to the community to use it as a side livelihood. One form of skill that may be given is the cultivation of natural eels because it is in line with the profession of the people of Rantau Baru Village as traditional fishermen. This training was attended by people from various occupational backgrounds, such as fishermen, laborers, entrepreneurs, temporary employees, and farmers. However, the participants who participated in the training were dominated by work as fishermen. The material provided in this training is the biology and behavior of eels by 28%, cultivation techniques by 27%, feeding techniques to eels by 27%, and post-harvest and marketing by 18%. After the training activities were given, there was an increase in participants' knowledge, excellent (69%) and sufficient (16%). The results indicate the success of participants in absorbing the material provided by the resource persons. The success in this training was also indicated by the evaluation results of 69.23% of participants stating that they understood well and 30.77% of participants stated that they understood. The success of delivering the material cannot be separated from the presentation of exciting material from the resource persons. The questionnaire filled out by the participants stated that 69.23% of participants stated that the delivery of the material was engaging, and 30.77% of the total participants stated that the delivery of the material was exciting. This eel cultivation training was also very beneficial for the participants, namely 84.62% of the total participants stated this training was beneficial. While 15.38% said, this training was valuable.